2009
DOI: 10.1182/blood-2009-07-231977
|View full text |Cite
|
Sign up to set email alerts
|

Significant functional heterogeneity among KIR2DL1 alleles and a pivotal role of arginine245

Abstract: Killer immunoglobulin-like receptors (KIRs) play an essential role in the regulation of natural killer cell functions. KIR genes are highly polymorphic in nature, showing both haplotypic and allelic variations among people. We demonstrated in both in vitro and in vivo models a significant heterogeneity in function among different KIR2DL1 alleles, including their ability to inhibit YT-Indy cells from degranulation, interferon ␥ production, and cytotoxicity against target cells expressing the HLA-Cw6 ligand. Sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
4
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 47 publications
4
119
4
3
Order By: Relevance
“…Secondly, the commonest KIR2DL1 allele on the B haplotype is KIR2DL1*004. This binds more weakly to HLA-C2 than KIR2DL1*003, the most common allele on the A haplotype [45]. We predict that there would be reduced inhibition of uNK cells by KIR2DL1*004 on the KIR B haplotype.…”
Section: Functions Of Uterine Natural Killer Cells During Placentationmentioning
confidence: 96%
“…Secondly, the commonest KIR2DL1 allele on the B haplotype is KIR2DL1*004. This binds more weakly to HLA-C2 than KIR2DL1*003, the most common allele on the A haplotype [45]. We predict that there would be reduced inhibition of uNK cells by KIR2DL1*004 on the KIR B haplotype.…”
Section: Functions Of Uterine Natural Killer Cells During Placentationmentioning
confidence: 96%
“…first reported that NK cells educated via KIR2DL1*004 had lower interferon‐ γ production than those educated via KIR2DL1*003 111. This occurs because KIR2DL1*004 has weak affinity for HLA‐C2 targets34 as well as reduced capacity for intracellular signal generation 112. A single dimorphism in the transmembrane region determines the signalling capacity; allotypes with R245 transduce a functional inhibitory signal and those with C245 have reduced inhibitory signalling 112.…”
Section: Kir Ligand Bindingmentioning
confidence: 99%
“…Nowadays, the easiest method to quantify NK cells expressing only one inhibitory KIR gene (i.e., negative for all other MHC inhibitory receptors) is multicolor flow cytometry (24)(25)(26) The third level of diversity is allele polymorphism, which has been observed in all inhibitory KIR genes (22,23). For example, in the KIR2DL1 family, 25 alleles have been observed, and each has different strengths in inhibiting NK cells and different durability of surface expression after interaction with ligands (27). These differences correlate with the intensity of inhibitory signaling through SHP2 and b arrestin-2, resulting in differences in immune synapse formation.…”
Section: Regulatory Receptorsmentioning
confidence: 99%
“…Mechanistically, the arginine residue at position 245 in the transmembrane domain is important in inhibition. Alleles with arginine in position 245 are stronger than those with cysteine in that position (27). On the basis of this molecular determinant, single-nucleotide polymorphism assays have been developed for rapid, high-throughput clinical typing (28).…”
Section: Regulatory Receptorsmentioning
confidence: 99%